Development of Job Scheduling and Machine Loading System in FMS - Zaid Hikmat Yaqoub; Amjad Barzan Abdulghafour (Engineering and Technology Journal, 2012)
Manufacturing industries are rapidly changing from production of scale to production of scope characterized by short product life cycles and increased product varieties. This implies a need to improve the efficiency of job shops while still maintaining their flexibility. These objectives are achieved by Flexible manufacturing systems (FMS). The basic aim of FMS is to bring together the productivity of flow lines and the flexibility of job shops, this duality of objectives makes the management of FMS complex. In this research, the loading problem in FMS, which is viewed as selecting a subset of jobs from the job pool and allocating them among available machines, is considered. The research investigates the number of machine loading approaches, which aim to meet the delivery dates of production orders, and at the same time reduce the manufacturing cost.